"Someone's generosity has formed a bond between us": Interpersonal relationships in Internet‐facilitated peer‐to‐peer milk sharing. (27th December 2018) - Gribble, Karleen
Abstract: Internet‐facilitated peer‐to‐peer milk sharing enables the giving and receiving of human milk between individuals previously unknown to one another. However, the process of milk sharing allows for milk sharing partners to develop relationships with one another. The development of relationships between 41 milk recipients and 97 milk donors in Internet‐facilitated peer‐to‐peer milk sharing was explored via a questionnaire. Thirty‐seven recipient respondents and 55 donor respondents placed some level of importance on developing a relationship with their milk sharing partner. Thirty‐four recipient respondents and 48 donor respondents had developed a relationship with at least one milk sharing partner, from acquaintanceship to close friendship. Respondents also described milk kinship relationships. Friendships were commonly noted as a positive repercussion of milk sharing. Milk sharing stigma was the only commonly reported negative repercussion of milk sharing. Peer‐to‐peer milk recipients and donors are forced by circumstance and encouraged by the process of milk sharing and by their similarity to one another to trust each another, which acts as a catalyst to friendship development. Peer‐to‐peer milk sharing is a type of cooperative mothering wherein milk recipients are assisted in parenting their children via the gift of milk. However, reciprocity is evident as milk donors benefit from good feelings from helping another mother and child, pleasure through seeing the recipient infant grow, and often friendship with their milk recipient. Although Internet‐facilitated peer‐to‐peer milk sharing is instigated by the impersonal medium of the Interweb, each milk sharing connection has the potential to become a real relationship.